Ethno Medicinal Plants of Reasi Tehsil of Reasi District, Jammu and Kashmir (India) - Singhal, Parul; Sharma, Vasundra (Indian Forester, 2020)
An ethno botanical survey was carried out in Reasi Tehsil of Reasi district, Jammu and Kashmir and 37 plant species belonging to 23 families were reported to treat various diseases. It mainly includes Reasi proper and its adjacent areas. Tehsil is a treasure house of highly valuable medicinal plants. Most of the plant species used were trees (37.83%) followed by herbs (35.15%), shrubs (24.32%) and climber (2.70%). The medicinal preparations include powder, decoction, juice, etc. The present study explores the wealth of traditional medicinal plants used by the local inhabitants of the study area against various diseases. The foremost purpose of the work done is to explore the potential of medicinal plants and reveal the rich diversity of the region which will be helpful for Traditional Knowledge Digital Library also.